DIFERENSIASI KEBIJAKAN BAIL OUT TERHADAP STABILITAS PERBANKAN - Agustine Sri Pamungkas; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research would explain the difference of bailout policy by England and United States of America in facing global financial crisis in 2008. This research use qualitative method and economic political perspectives. This research takes the range of time from 2009 until 2010 where in that year was a condition after buying bailout found by England and United States of America.Bail out is a term used to explain about situation for the bankrupt entity or almost bankrupt, like a company or a Bank by giving a liquid fresh fund injection. It can be said simply that bailout is a direct government intervention in economy. According to Keynes, government intervention is needed in economy minimal in the form of policy.As countries with liberal economy, America and England have different bailout policy orientation to solve Subprime mortgage case. Subprime mortgage case was assumed as a trigger of this financial crisis. Bail out done by America refers to save their corporations and strengthen their economy in the future without damaging the system of liberal they believe. In spite of that England disposed to save their corporations and economy that was to side with the society, to avoid rush and public trust. As a result, England bail out was faster than America in decreasing crisis fluctuation by giving big budgeting. America was not as faster as England in decreasing crisis fluctuation because of the difference of time in giving bail out, bail out’s funding, corporations that should be given bail out, and another obstacle in the parliament.Key words: financial crisis, subprime mortgage, economic policy, bailout